2008
DOI: 10.1016/j.neuropsychologia.2007.11.035
|View full text |Cite
|
Sign up to set email alerts
|

fMRI activation during episodic encoding and metacognitive appraisal across the lifespan: Risk factors for Alzheimer's disease

Abstract: In the present study, we used fMRI to examine the influence of age on two other known risk factors for Alzheimer's Disease (AD), APOE genotype and parental history of AD (FH status), during episodic encoding (ENC) and metacognitive self-appraisal (SA) paradigms. These paradigms have previously been shown to evoke activity from brain regions that are implicated in AD. First we examined the effect of age across the adult lifespan (age 18 to 84) on cerebral activity in a large sample (n=231) of cognitively health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 38 publications
3
44
1
Order By: Relevance
“…Elevated hippocampal activation observed on fMRI has also been reported in a number of other conditions that confer risk for AD including cognitively normal carriers of the ApoE-4 allelic variation (Bookheimer et al, 2000, Trivedi et al, 2008, Filippini et al, 2009, Dennis et al, 2010). ApoE-4 is the largest known genetic risk factor for sporadic AD (Corder et al, 1993) and increased hippocampal activation has been observed in ApoE-4 carriers decades before any cognitive symptoms would be expected to appear (Bookheimer et al, 2000, Burggren et al, 2002).…”
Section: Introductionmentioning
confidence: 71%
“…Elevated hippocampal activation observed on fMRI has also been reported in a number of other conditions that confer risk for AD including cognitively normal carriers of the ApoE-4 allelic variation (Bookheimer et al, 2000, Trivedi et al, 2008, Filippini et al, 2009, Dennis et al, 2010). ApoE-4 is the largest known genetic risk factor for sporadic AD (Corder et al, 1993) and increased hippocampal activation has been observed in ApoE-4 carriers decades before any cognitive symptoms would be expected to appear (Bookheimer et al, 2000, Burggren et al, 2002).…”
Section: Introductionmentioning
confidence: 71%
“…Several studies from our group and others have suggested that family history of AD is associated with preclinical brain changes (Bassett et al, 2006; Fleisher et al, 2009; Johnson et al, 2006, 2007; Schmitz et al, 2004; Trivedi et al, 2007; Xiong et al, 2011; Xu et al, 2009a). Based on prior findings with regard to risk, and patterns observed in AD and mild cognitive impairment, we expected that parental family history of AD would be associated with lower FA, and higher diffusivities.…”
Section: Discussionmentioning
confidence: 87%
“…Since electrical networks are prominently involved in memory formation, it is proposed that soluble Ab-induced perturbation of neuronal network activity, which induces dysfunction and memory deficits, may be a major and early contributor to AD pathogenesis. Consistent with this view, evidence from high-resolution fMRI in humans indicates, elevated hippocampal activation is observed in conditions that confer risk for Alzheimer's disease, including amnestic mild cognitive impairment [9]. On converse, reduction of hippocampal hyperactivity improves cognition in amnestic mild cognitive impairment [10].…”
Section: Introductionmentioning
confidence: 83%